Application of M5P Model Tree and Artificial Neural Networks for Traffic Noise Prediction on Highways of India - Mann, Suman; Singh, Gyanendra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Traffic noise prediction is the fastestgrowing development that reflects the rising concern of noise as environmental pollution. Prediction of noise exposure levels can help policy makers and government authorities to make early decisions and plan effective measures to mitigate noise pollution and protect human health.
Keywords: machine learning; M5P model tree; artificial neural networks; traffic noise